Avaliação do desenvolvimento motor de crianças de zero a dezoito meses de vida - Silva, Larissa Paiva (2013)
The accompaniment of infant development is considered one of the most important initiatives to reach a better quality of life. We sought to evaluate motor development in babies aged zero to 18 months. This is a descriptive, transversal and evaluative study performed in Health Family Centers (CSF) of the municipalities of Fortaleza and Sobral CE), Brazil. The sample was composed of 330 children, 165 from each studied municipality. Data collection took place between February/March 2012 through a predetermined form with child and family variables using the Alberta Infant Motor Scale (AIMS), Portuguese version and the Ministry of Health Control Protocol included in the Child Health Booklet (CSC), after approval granted by the Research Ethics Committee. According to results, in the Fortaleza municipality, most children were females born through cesarean section whereas in Sobral there was a predominance of males and natural births. In Fortaleza, 7.2% of children were premature and 6.6% had lower weight at birth while in Sobral, 8.5% were premature and 8.5% were born with low weight. As for the socioeconomic and educational profile of children’s parents/tutors, we found that in both municipalities the majority of them had 11 to 13 years of study, were aged 22 to 35 and did not have a paid occupation. With regards to their socio-demographic profile, most of them had basic sanitation, garbage collection service and ceramic floors. Child motor development was evaluated through the AIMS scale in both municipalities and it was considered normal for most children (307). This was corroborated by the second evaluation, made by the Ministry of Health Control Protocol (CSC) (302 children). The analysis of both documents showed agreement between them, however weak (k=0096; 0.077). When analyzing both results separately, we noticed more concordance among development deficit items. Different evaluation items were identified as “With deficit” or Without Deficit”, resulting in an almost perfect concordance (k=0.879; 0.910) between both instruments. There was also an important connection between the gestational age (p=0.012; 0.000) and the weight at birth (p=0.000; 0.000), considering the complete sample for both documents. We also found a relevant concordance between motor development when considering the full sample and risks factors associated to hospitalization, oxygen therapy and phototherapy. The maternal age showed a significant correlation in Fortaleza (p=0.001; 0.004). The analysis of the full sample (p=0.017; 0.016), the marital status (p=0.054; 0.049) and paid occupations in Sobral (p=0.003; 0.013), also resulted to be closely related to the scale qualifications. As for socio-demographic data, no statistically significant associations were found with regards to development levels according to the evaluation instruments. There was no difference between the children’s motor performance in the two studied municipalities. Both instruments presented high concordance levels in deficit detection and a significant correlation with infant mobility considering the following variables: gestational age, weight at birth, hospitalization, oxygen therapy, phototherapy, maternal age, marital status and mother paid occupation.